In-situ synthesis of Zr-based bulk metallic glass composites with periodic amorphous-crystalline microstructure for improved ductility via laser direct deposition. (August 2019) - Liu, Shunyu; Dhiman, Abhijeet; Shin, Yung C.; Tomar, Vikas; Zhang, Samuel T.
Abstract: In this paper, design and synthesis of in-situ ZrCuNiAl bulk metallic glass composites (BMGC) from premixed metal powders were achieved using laser direct deposition (LDD). The temperature fields and heating/cooling rates in single-track BMGC were simulated through a validated LDD model, which provided insights for microstructure evolution. Through a proper selection of LDD parameters and precise control of premixed composition, a periodic amorphous-crystalline microstructure was obtained alternatively in the fusion zone (FZ) and heat affected zone (HAZ). In addition to HAZ, composite phase nature was also achieved in FZ where about 4.7 vol% crystals with a size of 100–1000 nm were uniformly formed in the amorphous matrix. Vickers microhardness revealed a higher hardness of 620 HV0.2 in FZ than 450 HV0.2 in HAZ. An optimized overlapping ratio of adjacent tracks at 58 vol% led to 89 vol% FZ in the bulk structure, which resulted in an overall macrohardness of 604 HV. Nanoindentation tests were performed to study the deformation behavior at the micron/sub-micron length scale. The depth-sensing indentation stress-strain data in FZ and HAZ were accurately predicted with an iterative numerical algorithm using finite-element modeling. A correction factor was proposed in this algorithm, which corrected the overestimation of experimental stress by minimizing the difference between experimental and numerical load-depth data. With the composite microstructure, an indentation strain of more than 13% was obtained in both zones. Graphical abstract: Image 1 Highlights: ZrCuNiAl metallic glass composites with high ductility are in-situ synthesized by laser direct deposition. Premixed metal powders are used to prepare the ZrCuNiAl precursor powder. A periodic amorphous-crystalline structure is formed due to the thermal history. Crystalline phases improve plasticity up to at least 13% while the amorphous phase maintains strength.